Atrial fibrillation in patients with acute coronary syndrome under clopidogrel versus ticagrelor. (26th April 2021) - Almeida, I; Santos, H; Santos, M; Miranda, H; Chin, J; Sousa, C; Almeida, L
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Portuguese Registry of Acute Coronary Syndromes (ProACS) Introduction: Ticagrelor is a drug widely used in patients with acute coronary syndromes (ACS) that increases the plasma level of adenosine, which can lead to the development of atrial fibrillation (AF). Objective: Evaluation of AF development in patients medicated with clopidogrel versus ticagrelor. Material and methods: Retrospective analysis of patients admitted with ACS included in the Portuguese Registry of Acute Coronary Syndromes (ProACS) between 2010-19. Patients were divided in two groups regarding the development of de novo AF. The role of ticagrelor vs clopidogrel in AF induction was compared. In-hospital outcomes were evaluated. Results: 25727 patients were included, mean age 67 ± 14 years, 72.3% male. 3.6% (n = 1067) presented de novo AF (of which 18.1% at emergency department admission). They were older (75 ± 12 vs 66 ± 14, p < 0.001), with more classic cardiovascular risk factors except for smoker status and family history of premature cardiovascular disease, with less previous cardiovascular disease although more cerebrovascular peripheral vascular disease. They presented more frequently with STEMI (53.4 vs 41.9%, p < 0.001) vs NSTEMI/ unstable angina or indetermined infarction. They presented lower systolic blood pressure (131 ± 30 vs 139 ± 28mmHg, p < 0.001), higher heart rate (85 ± 27 vs 77 ± 18bpm, p < 0.001) and Killip-Kimball (KK) class (KK class >I 35.6 vs 14.3%, p < 0.001) and had less kidney dysfunction (maximum creatinine 1, 1 ± 0, 4 vs 0, 9 ± 0, 4mg/dl, p < 0.001). Most patients (53.4%) were medicated with the clopidogrel P2Y12 inhibitor. However, 20.4% of patients who developed AF were medicated with ticagrelor versus 5.7% with clopidogrel. Left anterior descendent (LAD) was the most prevalent culprit vessel in both groups (40.9 vs 37.2%, p = 0.045). Multivessel disease was more prevalent in AF group (56.0 vs 51.5%, p = 0.011) and they needed more frequently advanced therapeutic devices and ventilatory support. In-hospital complications were also more frequent in AF patients: heart failure (45.7% vs 14.3%, p < 0.001), cardiogenic shock (16.1% vs 3.6%, p < 0.001), cardiopulmonary arrest (9.2 vs 2.4%, p < 0.001) and death (11.0 vs 3.4%, p < 0.001). Conclusion: In our study, there was a trend to de novo AF development in patients admitted with ACS and medicated with ticagrelor versus clopidogrel.